ByzRev 07.2025.064: Conor Whately (ed.), Military Literature in the Medieval Roman World and Beyond: (Reading Medieval Sources 8). Leiden: Brill 2024. - Rance, Philip (The Byzantine Review, 2025)
Conor Whately (ed.), Military Literature in the Medieval Roman World and Beyond (Reading Medieval Sources 8). Leiden: Brill 2024. xiii, 454 pp. – ISBN 978-90-04-69373-9